Design and Hardware Implementation of Buck Converter Solar Charge System Using PID Controller - Widi Dionova, Brainvendra; Suryo Jati, Cahyo Wibisono; Wilyanti, Sinka; Restuasih, Sinta; Vresdian, Devan Junesco; Ikmal (Jakarta Global University, 2022)
Nowadays, energy sources in the world at the end until now tends to be filled using fossil fuels. It is estimated that the world energy consumption until 2025 is still dominated by fossil fuels, namely oil, natural gas and coal. The Ministry of Energy and Mineral Resources said that petroleum dominates 54% of energy use in Indonesia. One way to overcome the use of fossil energy sources is to replace them with renewable energy especially photovoltaic. Therefore, this paper presents solar charge system using Buck Converter PID Controller for Spotlight load. Buck Converter with PID Controller is used to produce a smaller and more stable output voltage from solar panels of 14.4 Volts for charging the battery. The PID parameter values ​​obtained after performing calculations using the Analytic Tuning method and tuning are Kp = 0.0307, ​​Ki = 58.20 and Kd = 0.000263. The expected result of this research is to design and implement a solar charge controller as a producer of electrical energy from environmentally friendly energy.